Assessing potentials exploring the experiences of students on the restorative potential of the campus green space - Abanes, Venice P.; Dacdac, Cherey Mie A.; Sabangan, Camille Joy P.; Sadian-Cercado, Ruth Edisel Rylle B.; Villadolid, Vincenette Brea E. (2024)
The academic journey of college students is often filled with stressors that can significantly impact their well-being. Existing studies on nature and well-being underscore the potential of green spaces within university campuses to offer a health-promoting effect. Yet, there is still limited research exploring how university students engage with these spaces, influences for their visitations, and the resulting restorative effects that they experience, particularly within the Philippine context. To address these gaps, the present study utilized a phenomenological approach to delve into the diverse perspectives of Filipino university students on the restoration potential of the campus green spaces. Through interviews and thematic analysis, the research delved into the multifaceted ways in which students engaged and utilized these natural environments. The findings revealed that students utilized the campus green spaces for various purposes, including recreational activities, socialization and academic pursuits. Furthermore, exposure to these green spaces is associated with a wide range of restorative effects such as enhanced cognitive function, bodily rejuvenation, and emergence of positive emotions. Upon assessing the findings, it was concluded that campus green spaces serve as spaces where students can perform their activities as well as gain psychological restoration.
Undergraduate thesis (B.A. Psychology) -- University of the Philippines, Tacloban.